Erythromycin Estolate Is a Potent Inhibitor Against HCoV-OC43 by Directly Inactivating the Virus Particle - Wang, Xiaohuan; Chen, Yongkang; Shi, Huichun; Zou, Peng (Frontiers in Cellular and Infection Microbiology, 2022)
In addition to antibacterial effects, macrolide antibiotics exhibit other extensive pharmacological effects, such as anti-inflammatory and antiviral activities. Erythromycin estolate, one of the macrolide antibiotics, was previously investigated to effectively inhibit infections of various flaviviruses including Zika virus, dengue virus, and yellow fever virus, but its antiviral effect against human coronavirus remains unknown. Thus, the current study was designed to evaluate the antiviral efficacy of erythromycin estolate against human coronavirus strain OC43 (HCoV-OC43) and to illustrate the underlying mechanisms. Erythromycin estolate effectively inhibited HCoV-OC43 infection in different cell types and significantly reduced virus titers at safe concentration without cell cytotoxicity. Furthermore, erythromycin estolate was identified to inhibit HCoV-OC43 infection at the early stage and to irreversibly inactivate virus by disrupting the integrity of the viral membrane whose lipid component might be the target of action. Together, it was demonstrated that erythromycin estolate could be a potential therapeutic drug for HCoV-OC43 infection.